Transitioning into Career Success: A Grounded Study on the Lifewide Learning Experiences of Successful High Potential Individuals in Early Adulthood - Joslyn Johnson (Adult Education Research Conference, 2018)
This qualitative study looked at the lifewide learning experiences of high potential individuals that were able to reach career success and have a sense of fulfillment in early adulthood (23-39).
Keywords: Lifewide Learning; High Potential; Purpose; Career Sucess; Early Adulthood